Beyond the Pesantren Gates: Exploring the Boarding School System at SMP Islam Al-Hadi Mojolaban - Sholikhah, Fatimah Nur; Rosyana, Fauziah Mursyid (Bestari, 2025)
This study investigates the implementation of boarding school management at SMP Islam Al-Hadi Mojolaban, focusing on three key aspects: operational practices, efforts to enhance learning quality, and the challenges encountered. A descriptive qualitative approach was chosen to deeply capture the complexity of the phenomenon, with data collected through participant observation, semi-structured interviews, and document analysis. Participants were initially selected purposefully, then expanded using snowball sampling to capture key perspectives that might not have been apparent in the initial stages. The research findings reveal that the management model at this institution is integrated, closely linking boarding life with school academic activities. In practice, management encompasses five main dimensions: student administration, teacher management, provision of facilities and infrastructure, program design, and evaluation mechanisms. Nevertheless, efforts to improve learning quality are not without challenges—some structural, others contextual—which, interestingly, provoke creative adaptations from stakeholders. This analysis provides a realistic overview of boarding school dynamics within an Islamic educational setting, simultaneously highlighting the gaps between theory and practice that often escape academic discussion. We note that the integrated approach adopted by SMP Islam Al-Hadi offers valuable insights, though it is not yet entirely optimal, particularly concerning resource allocation and curriculum adjustments.